Incidence and clinical features of congenital adrenal hyperplasia in Great Britain. Issue 2 (11th January 2012) - Khalid, Javaria Mona; Oerton, Juliet M; Dezateux, Carol; Hindmarsh, Peter C; Kelnar, Christopher J; Knowles, Rachel L
Abstract : Objectives: To estimate the incidence of clinically diagnosed congenital adrenal hyperplasia (CAH), clinical features and age at first presentation. To assess the potential benefit of newborn screening for CAH. Design: Active surveillance through the British Paediatric Surveillance Unit of all children aged under 16 years with newly diagnosed CAH, undertaken prospectively between August 2007 and August 2009. Twelve laboratories testing for CAH reported new diagnoses between August 2007 and January 2009. Reporting clinicians completed clinical questionnaires. Setting: England, Wales and Scotland. Results: 144 children with CAH were reported, of whom 132 (92%) had 21-hydroxylase deficiency. Thirty-six (25%) children were Asian and 62 (43%; 95% CI 35% to 51%) were boys. Incidence of new diagnoses in children ≤16 years was 0.60 (95% CI 0.50 to 0.71) per 100 000. Eighty-six (59%; 36 boys) children were diagnosed in the first year of life (estimated birth prevalence 5.48 (95% CI 4.42 to 6.81) per 100 000), most (77; 89%) of whom presented in the first month of life. Virilised genitalia were found in three-quarters of girls. Twenty-seven newborns first presented with salt-wasting crises, of whom 18 (67%; 16 boys) presented on or after 14 days of age. Conclusions: Approximately one child in every 18 000 born in Great Britain has CAH. Similar numbers of boys and girls present clinically in the first year of life, but boys present with more severe manifestations, such as salt-wasting crises. Around 70% of newborns who first present with salt-wasting crisis would be detected earlier through newborn screening.